Analisis Faktor Kualitas Pelayanan Customer service Prioritas terhadap Kepuasan Nasabah di BCA KCU Gading Serpong - Arie Rivaldi Gunawan; Fransiscus Amonio Halawa (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study aims to analyze the effect of priority Customer service quality on customer satisfaction at BCA KCU Gading Serpong using the five SERVQUAL dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The research employed a quantitative approach with a causal research design. The population consisted of 875 active priority customers, while the sample comprised 100 respondents selected using the Slovin formula through purposive sampling and quota sampling techniques. Data were collected using Likert-scale questionnaires and analyzed through multiple linear regression using SPSS version 25. The findings indicate that each SERVQUAL dimension has a positive and significant effect on customer satisfaction, with significance values below 0.05. Simultaneously, the five dimensions significantly influence customer satisfaction, as indicated by an F-value of 57.184, a significance level of 0.000, and a coefficient of determination of 71.9% (R² = 0.719). Among the five dimensions, Responsiveness has the strongest influence on customer satisfaction. Therefore, BCA KCU Gading Serpong is recommended to continuously improve service quality, particularly in Responsiveness, Reliability, and Tangibles, to maintain and enhance priority customer satisfaction.